Metabolic Response of the Immature Right Ventricle to Acute Pressure Overloading. Issue 11 (22 September 0207) - Kajimoto, Masaki; Nuri, Muhammad; Isern, Nancy G.; Robillard‐Frayne, Isabelle; Des Rosiers, Christine; Portman, Michael A.
Abstract : Background: Surgical palliation or repair of complex congenital heart disease in early infancy can produce right ventricular (RV) pressure overload, often leading to acute hemodynamic decompensation. The mechanisms causing this acute RV dysfunction remain unclear. We tested the hypothesis that the immature right ventricle lacks the ability to modify substrate metabolism in order to meet increased energy demands induced by acute pressure overloading. Methods and Results: Twenty‐two infant male mixed breed Yorkshire piglets were randomized to a sham operation (Control) or pulmonary artery banding yielding >2‐fold elevation over baseline RV systolic pressure. We used carbon 13 ( 13 C)‐labeled substrates and proton nuclear magnetic resonance to assess RV energy metabolism. [Phosphocreatine]/[ATP] was significantly lower after pulmonary artery banding. [Phosphocreatine]/[ATP] inversely correlated with energy demand indexed by maximal sustained RV systolic pressure/left ventricular systolic pressure. Fractional contributions of fatty acids to citric acid cycle were significantly lower in the pulmonary artery banding group than in the Control group (medium‐chain fatty acids; 14.5±1.6 versus 8.2±1.0%, long‐chain fatty acids; 9.3±1.5 versus 5.1±1.1%). 13 C‐flux analysis showed that flux via pyruvate decarboxylation did not increase during RV pressure overloading. Conclusions: Acute RV pressure overload yielded a decrease in [phosphocreatine]/[ATP] ratio, implying that ATP production did not balance the increasing ATP requirement. Relative fatty acids oxidation decreased without a reciprocal increase in pyruvate decarboxylation. The data imply that RV inability to adjust substrate oxidation contributes to energy imbalance, and potentially to contractile failure. The data suggest that interventions directed at increasing RV pyruvate decarboxylation flux could ameliorate contractile dysfunction associated with acute pressure overloading.